Estudio bromatológico y microbiológico de vienesa, utilizando diferentes formulaciones de extracto de pimiento rojo (Capsicum annuum) - Quezada Salas, Adriana Gissela (2015)
The present research work was conducted in Loja in the experimental meat prick of Agricultural and Natural Resources area farm that belongs to the “ Universidad Nacional de Loja” , with the purpose to elaborate Viennese using different ingredients of red pepper (0.06 % - 0.08 % and 0.1 % ) , It is used as a natural antioxidant as well as the use of sodium erythorbate as the control treatment with three replicates per treatment , an experimental unit size of 8 mass kg per replicate was used. Once developed and obtained the product assessment and organoleptic assessment was used with 10 students of the eighth module Career Veterinary Medicine and Animal Science, with greater acceptance treating 0.1%, although the total value all achieved a rating good, and food science and microbiological analysis. Bromatological the analysis performed in the laboratory of Food Science and Soils of the National University of Loja and microbiological laboratory analysis of food analysis (MSV) of the city of Cuenca. As a result of this investigation it was determined that the formulation of higher T3 acceptability was 0.1%, the results of the physical, bromatological and microbiological analysis can confirm that the Viennese made with natural antioxidant is fit for human consumption as These values are within the limits permitted by the INEN quality standard. Key Words: Viennese, natural antioxidant, nutrition analyzes, microbiological analyzes.